Huy, ang taba mo na a descriptive study on the relationship of body shaming, self-esteem, and self-consciousness of self-declared plus-size women - Tibi, Nichole; De Luna, Teresa Paula S. (Quezon City College of Arts and Letters, University of the Philippines Diliman, 2019)
This descriptive study, utilizing both quantitative and qualitative methods, aimed to establish the relationship among the frequency of body shaming, the level of self-esteem, and the level of self-consciousness of self-declared plus-size women from the university of the Philippine Diliman using E. Tory Higgins' Self Discrepancy Theory and to probe deeper as to why such relationship transpires through Carl Roger's Self Theory. The researcher employed the Rosenberg Self- Esteem Scale (Rosenberg, 1965) and the Self- Consciousness Revised Scale (Scheier & Carver, 1985), and conducted a pilot study to be able to create a scale that aided the researcher in identifying how often the respondents experience body shaming. A focused group discussion was facilitated with five out of 60 respondents that answered the survey to support discussion and analysis of the findings.60 female undergraduates aged 18-22 who perceive themselves as plus-size were surveyed and the following results were obtained. Results revealed that self-declared plus-size women receive 11 different types of body shaming remarks from other people. Results also showed that while most self-declared plus-size women experience being body shamed 1-3 times a week to once every two weeks, they scored low in the level of self-esteem and normal in the level of self-consciousness. Contrary to the hypotheses of this study that were derived from the related literature and studies, findings revealed that there are no significant relationships among the frequency of body shaming experiences of the respondents, the level of their self-esteem, and the level of their self-consciousness. It could be explained through a certain finding that had emerged upon analyzing the results and reviewing the related literature and studies that women differ in terms of their reactions and resilience when they encounter threats to their self-esteem and self-consciousness such as body shaming.
Thesis (B.A. in Speech Communication)--University of the Philippines Diliman
Includes bibliographical references and appendices.